Exhibiting Creative Geographies Bringing Research Findings to Life - Boyd, Candice P. (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This open access book provides a detailed example of arts-based knowledge translation from start to finish for any scholar interested in communicating research findings through art. Firmly grounded in the GeoHumanities, a field at the intersection of cultural geography and the arts, this book explores the theory and practice of research exhibitions. Commencing with an overview of arts in health and art-science collaborations, this book also explores the concept of 'affective knowledge translation'. In doing so, it describes the creative co-production, staging, and evaluation of the Finding Home exhibition which toured Australia during 2021. As a demonstration of the power of art to engage audiences, raise awareness of social issues, communicate lived experience, and extend the reach of cultural geographic research, this book is relevant to academics from any discipline who are keen to increase the societal impact of their work. Candice P. Boyd is an artist-geographer and Australian Research Council DECRA Fellow at the University of Melbourne, Australia. She is the author of Non-Representational Geographies of Therapeutic Art Making, co-editor of Non-Representational Theory and the Creative Arts, and co-author of Emotion and the Contemporary Museum, all published with Palgrave Macmillan. .